REFORMULASI TERHADAP PENGATURAN UJARAN KEBENCIAN (HATE SPEECH) MELALUI MEDIA SOSIAL DI INDONESIA - suci jolanda; Evi Deliana; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The development of information and communication technology is now increasingly sophisticated with the emergence of various kinds of social media. Many users of social media abuse by spreading false news bringing down others and even spreading hate speech that can harm a group. The rise of hate speech (hate speech) is increasingly gaining attention from the public and law enforcement officials. Hate speech can encourage incitement, discrimination, violence, and even national divisions. The Electronic Information and Transaction Law (ITE Law) is a law that regulates hate speech on social media. In these laws the object of a criminal offense needs attention, because information intended to incite hatred is very biased in interpretationThis type of research can be classified into types of researchers Normative research or what is known as